The Relationships between Crude Oil Prices, Financial Performances and Share Prices of Oil and Gas Producers - Liu, Ying Gui (2014)
The paper investigates the relationships between crude oil prices, financial performances and share prices of 233 studied oil and gas producers. Hamilton's (2003) study emphasized the significant correlation between increases in crude oil prices and US recessions. Hamilton (2010) also pointed out that almost all major economic downturns have been immediately preceded by a significant rise in oil prices. This study collects and uses all of the 233 worldwide listed oil and gas producers’ monthly, quarterly and yearly accounting (Book Value, Earnings Per Share and Earnings Before Interest and Taxes) and stock market information that could be found in the Datastream Advance database. This study has assessed and analyzed the impacts of crude oil prices on both the studied firms’ financial performances and their share prices. The empirical evidence suggested a significant positive correlation amongst crude oil prices and the studied firms' stock market performances and their financial performances. A significant and very strong correlation also exists between the studied firms' financial performances and their stock market performances. This finding is aligned with that studied for the forward relationship between crude oil prices and the stock market performances. An increase in crude oil prices leads to a higher stock market revenues, and vice versa, a falling crude oil prices cause a decrease in their market share values.